Internal audits as a tool to assess the compliance with biosecurity rules in a veterinary faculty - Humblet, Marie-France; Saegerman, Claude (Frontiers in Veterinary Science, 2023)
The present paper proposes a tool to follow up the compliance of staff and students with biosecurity rules, as enforced in a veterinary faculty, i.e. animal clinics, teaching laboratories, dissection rooms, and educational pig herd and farm. Starting from a generic list of items gathered into several categories (personal dress and equipment, animal-related items, infrastructures, waste management, management of material/equipment and behaviour), a checklist was created for each sector/activity mentioned above, based on the rules and procedures compiled in the Faculty biosecurity standard operating procedures. Checklists were created under the form of Excel™ files. For each sector, several sheets were elaborated, i.e. one per specific activity: for example, the following sheets were created for the equine clinic: class 1-2 hospitalization (class 1 = non-infectious conditions; Class 2 = infectious disease with a low or non-existent risk of transmission), class 3 hospitalization (class 3 = infectious disease with a moderate risk of transmission; these patients are suspected of having an infectious disease and being contagious for other patients and/or for humans) and consultation. The audit relied on observations performed by a unique observer to ensure standardization. Observed items were presented as multiple choice- and binary questions. A scale from 0 to 3 or 4 (depending on the item) allowed scoring each item, i.e. 0 corresponding to 100% compliance with the procedure and the highest score to the worst situation. A median and average global score was also estimated per category and per activity. The methodology described in the present paper allows estimating the compliance with biosecurity standard operating procedures in a specific sector and/or for a given activity. The identification of criteria needing improvement is a key point: it helps prioritizing actions to be implemented and awareness raising among people concerned. Regular internal auditing is an essential part of a biosecurity plan.